Assessment of the Magdalena River delta socio-ecological system through the Circles of Coastal Sustainability framework - Gallo-Vélez, David; Restrepo, Juan Camilo; Newton, Alice (Frontiers in Earth Science, 2023)
River-mouth systems and deltas are hotspots where many of the coastal syndromes can be found. Moreover, these systems provide essential ecosystem services (e.g., recreation, food provisioning, protection against natural hazards). The present study focuses on the socio-ecological system (SES) at the delta of the Magdalena River in the central Caribbean Region in Colombia. This research seeks to assess the multidimensional sustainability of the Magdalena river-mouth system (MRm-SES) to improve the knowledge basis for its integrated management. To do so, an assessment tool named ‘Circles of Coastal Sustainability’ (CCS) was used to evaluate the system splitting it into four domains (environmental, social, economic and governance) that were divided into 5 categories each. These domains were evaluated through a total of 52 indicators distributed like this: 16 for the Environmental domain, 16 for the Economic domain, 12 for the Social and Cultural domain and, 8 for the Governance domain. The results show that the overall sustainability of the MRm-SES is classified as ‘Satisfactory’. None of the domains is in ‘Excellent’ or ‘Bad’ conditions. However, the evaluation of the categories shows that four (4) of them have ‘Poor’ conditions (i.e., Social Benefits, Demographics, Economic Security, and Resources Management). Hence, it is recommended to put those categories at the centre of the discussion to define management strategies (e.g., Preserving and restoring habitats; tackling sources of pollution and excessive sediment; local reduction of net GHG and adaptation to climate change; participation of local communities in the management design and implementation) without disregarding the interrelation with the other categories and dimensions. Finally, it is argued that despite all the improvement opportunities, the CCS is a valuable tool to evaluate and communicate, with different stakeholders (academic community, managers and decision-makers, local communities, etc.), the sustainability of coastal systems in Colombia and the world.